2020
DOI: 10.3390/nu12092565
|View full text |Cite
|
Sign up to set email alerts
|

Association between Infant and Young Child Feeding (IYCF) Indicators and the Nutritional Status of Children (6–23 Months) in Northern Ghana

Abstract: Although recommended infant and young child feeding (IYCF) practices have been found to be protective against undernutrition in some settings, there is no finality yet due to inconsistencies in the literature. A cross-sectional survey of 581 mother-child pairs was conducted in northern Ghana in June 2018. The association between IYCF indicators and child undernutrition (stunting and wasting) were assessed. The descriptive analysis showed that 66.4% of the children (6–23 months) were introduced to complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 53 publications
6
34
1
1
Order By: Relevance
“…This finding implies that countries that have high prevalence should take critical lessons from the countries that are doing well regarding the implementation of nutritional policies and interventions (eg, increasing dietary supplementation, increasing dietary diversity) that target the reduction of the coexistence of stunting, underweight and wasting among children under age 5 in SSA. 2 Similar to previous studies, 1 3 we found that children aged 1 year, 2 years and 3 years were at greater risk of Open access Open access having coexistence of all the three forms of undernutrition compared with those aged 0. This could be as a result of the fact that as children grow their energy needs also increase 1 thereby increasing their risk of having all three nutritional conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding implies that countries that have high prevalence should take critical lessons from the countries that are doing well regarding the implementation of nutritional policies and interventions (eg, increasing dietary supplementation, increasing dietary diversity) that target the reduction of the coexistence of stunting, underweight and wasting among children under age 5 in SSA. 2 Similar to previous studies, 1 3 we found that children aged 1 year, 2 years and 3 years were at greater risk of Open access Open access having coexistence of all the three forms of undernutrition compared with those aged 0. This could be as a result of the fact that as children grow their energy needs also increase 1 thereby increasing their risk of having all three nutritional conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Undernutrition among children under 5 years remains a major public health problem across many low-income and middle-income countries. [1][2][3] Factors such as insufficient food intake, diarrhoea, recurring infections, poor sanitation practices, and low parental education have been identified as significant contributors to the high prevalence of undernutrition during childhood. 1 4 5 Despite the numerous interventions rolled out to address childhood undernutrition especially in sub-Saharan Africa (SSA) where the phenomenon is quite pervasive, the progress seems to be insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary diversity is considered to be an outcome of the nutritional status of children [3,4] and a key component of high-quality diets [5][6][7]. Dietary diversity is used as a tool to measure dietary quality, micronutrient adequacy, and food access [8][9][10][11] and it influences the health outcomes of children under five [3,12]. Studies show that inadequate dietary quality and diversity lead to undernutrition including stunting, underweight, and wasting [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends that young children, especially infants should receive a minimum of four out of the seven groups of foods-namely: grains, roots, and tubers; legumes and nuts; dairy products; flesh foods (meat, fish, poultry, and organ meats); eggs; vitamin-A-rich fruits and vegetables; and other fruits and vegetables [5,14,15]-to maintain proper growth and development [15]. Yet, many children in low-and middle-income countries do not have adequate dietary diversity [8][9][10][11]. Less than one-fourth of children aged 6-23 months met the minimum acceptable diet dietary diversity and meal frequency standards in low and middle-income countries [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation